Drones : the brilliant, the bad and the beautiful - Miah, Andy, 1975- (SocietyNow., 2020)
Against the backdrop of an increasingly dynamic world, driven by rapid digital innovation and technological advances, drones are becoming prolific within society. In this book, Andy Miah delivers a comprehensive analysis of the wide-reaching applications of drones, as well as a critical interrogation of the social, cultural and moral issues that they provoke. Delving into philosophical discussions about the implications of drone technology, this book shines a light on their real-world applications, the challenges they pose, and what they reveal about the human condition, when faced with a future of autonomous, intelligent robots.